Measurement of ammonia emission from agricultural sites using open-path cavity ring-down spectroscopy and wavelength modulation spectroscopy based analyzers - Shadman, Soran, author; Yalin, Azer P., advisor; Marchese, Anthony J., committee member; Olsen, Daniel B., committee member; Ham, Jay, committee member (Colorado State University. Libraries, 2018)
Agricultural activities and animal feedlot operations are the primary sources of emitted ammonia into the atmosphere. In the US, 4 Tg of ammonia is emitted every year into the atmosphere which ~%75 of that is due to these major sources. Ammonia is the third most abundant nitrogen containing species in the atmosphere and it has important impacts on atmospheric chemistry, health, and the environment. It is a precursor to the formation of aerosols and its deposition in pristine and aquatic systems leads to changes in ecosystem properties. Quantifying the dry deposition rate of ammonia in the first few kilometers of feedlots is crucial for better understanding the impacts of livestock and agricultural operations on environment. Therefore, fast, precise, and portable sensors are needed to quantify ammonia emission from its major sources. Absorption spectroscopy is a reliable technique by which compact and sensitive sensors can be developed for ammonia (and other gaseous species) detection. An open-path absorption spectroscopy based sensor allows ambient air to flow directly through its measurement region which leads to high-sensitivity and fast-response measurements. In this study, two open-path absorption based ammonia sensors using two techniques are developed: cavity ring-down spectroscopy (CRDS) and wavelength modulation spectroscopy (WMS). The CRDS and WMS based sensors show the sensitivity of ~1.5 ppb (at 1 second) and ~4 ppb (at 1 second), respectively. In both sensors, a quantum cascade laser (QCL) is utilized as the light source to cover the strongest absorption feature of ammonia in the mid-infrared (MIR) spectral region. It is the first demonstration of an open-path CRDS based sensor working in mid-infrared MIR, to our knowledge. The WMS based sensor developed in this study is low power (~25 W) and relatively lightweight (~4 kg). The low power consumption and compact size enables the sensor to be deployed on a commercialized unmanned aerial system (UAS) for aerial measurements. The combination of this sensor and another compact CRDS based methane sensor is used for simultaneous measurements of ammonia and methane (ground based and aerial). Methane is another important species emitted from the feedlots with a long lifetime (~10 years). It is nonreactive and thus not lost by dry deposition. Therefore, methane concentration is only influenced by dispersion while the ammonia concentration is affected by both deposition and dispersion. The dry deposition of ammonia nearby the concentrated animal feeding operations (CAFOs), as one of the major sources of ammonia, can be determined by measuring the decrease in the [NH3]/[CH4] ratio downwind.
Keywords: laser; air pollution; spectroscopy